Multilingual America : language and the making of American literature - Rosenwald, Lawrence Alan, 1948- (Cambridge studies in American literature and culture ;, 2008)
"Throughout its history, America has been the scene of multiple encounters between communities speaking different languages. Literature has long sought to represent these encounters in various ways, from James Fenimore Cooper's frontier fictions to the Jewish-American writers who popularized Yiddish as a highly influential modern vernacular. While other studies have concentrated on isolated parts of this history, Lawrence Rosenwald's book is the first to consider the whole story of linguistic representation in American literature, and to consider how multilingual fictions can be translated and incorporated into a national literary history."--Jacket